Simulation development content for students employ ability in logistics and transportation field in Malaysia - Zainuddin, Nizamuddin; Mohd Saifudin, Adam; Bahaudin, Ahmad Yusni; Zalazilah, Mohd Hanizan; Jamaludin, Roslan (ExcelingTech Publishers, 2016)
Simulation is all about representing the real world which includes grasping the complex issues and solving intricate problems, and it affects student’s employ ability rate in a way of preparing the students.Base on the market needs. This paper will look into simulation.Content development, which is all about developing, enriching and the applications of the Internet protocol in order to enrich the work related competencies experience among graduate in the field of logistics and transportation's and will focus on the real challenges' inputs to the generic workflow of the simulation content development.The study was carried out within multi-national and local manufacturing companies, third party companies (3PL) and government agency, which are selected from Peninsular Malaysia.A qualitative approach was mainly conducted to gather data in the study.It was then discovered from the study that the systems used in the process of outbound and inbound are System Application Products (SAP) and Material Requirement Planning (MRP).It was further discovered that there are only four companies using Enterprises Resources Planning (ERP) and Electronic Data Interchange (EDI) as part of the Suppliers Own Inventories (SOI) networking as a result of globalized business between one country to another.The study contributes to the body of knowledge on the enrichment of the student’s employability.